The forgotten emancipator : James Mitchell Ashley and the ideological origins of reconstruction / Rebecca E. Zietlow. - Zietlow, Rebecca E. (Cambridge historical studies in American law and society., 2018)
Congressman James M. Ashley, a member of the House of Representatives from 1858 to 1868, and was the main sponsor of the Thirteenth Amendment to the American Constitution, which declared the institution of slavery unconstitutional. Rebecca E. Zietlow uses Ashley's life as a unique lens through which to explore the ideological origins of Reconstruction and the constitutional changes of this era. Zietlow recounts how Ashley and his antislavery allies shared an egalitarian free labor ideology that was influenced by the political antislavery movement and the nascent labor movement - a vision that conflicted directly with the institution of slavery. Ashley's story sheds important light on the meaning and power of popular constitutionalism: how the constitution is interpreted outside of the courts and the power that citizens and their elected officials can have in enacting legal change. The book shows how Reconstruction not only expanded racial equality but also transformed the rights of workers throughout America.